الحكومة الإلكترونية في الجزائر بين الواقع والتحديات - يحياوي، إلهام (جامعة سطيف 1 - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2016)
تهدف هذه الدراسة إلى إبراز التجربة الجزائرية في مجال تطبيق الحكومة الإلكترونية، فالجزائر كبلد عربي تبنى الحكومة الإلكترونية استجابة لقرارات مؤتمر القمة العالمية لمجتمع المعلومات عام 2003 والذي تمخض عنه قرارات وتوصيات عديدة لخدمة العملية التربوية والحكم الرشيد والتي تصب أساسا في الحكومة الإلكترونية كإطار عام لتحقيق ذلك، فهي اتجهت نحو تطوير سياساتها العامة بما يتناسب مع معطيات العصر والتغيرات التكنو- اقتصادية والسياسية الجديدة وتطوير الآليات والوسائل التقنية المستخدمة في تنفيذها، إلا أنها واجهت ومازالت تواجه عدة تحديات وعراقيل عند التطبيق سنوضحها في متن الدراسة. توصلت الدراسة إلى أن تطبيق مشروع الجزائر الإلكترونية 2013 مرتبط بمدى التغلب على التحديات والرهانات التي تقف أمام هذا المشروع والذي يحتاج إلى المزيد من الفعالية حتى تستطيع تأدية دورها في خدمة المواطن الجزائري وترقية وتطوير الاقتصاد الوطني وتحقيق التنمية الشاملة. ومن بين أهم الاستخدامات الآنية للحكومة الإلكترونية في الجزائر: بطاقة الشفاء، البطاقة المغناطيسية (صفراء اللون)، بطاقة الدفع الإلكتروني (البطاقة الذهبية)، الجيل الثالث، الجيل الرابع، جواز السفر البيوميتري وبطاقة التعريف البيوميترية، أجهزة التكنولوجيا في الأمن الوطني.
This study aims to highlight the Algerian experience in the application of e-government, Algeria is a country Arabic adopt e-government response to the decisions of the World Summit on the Information Society in 2003 and which culminated in the decisions and recommendations of many to serve the educational process and good governance, that feed mainly in the e-government as a general framework to achieve this , they tended towards the development of public policies in line with the requirements of the times and changes techno - economic, political, new, and the development of mechanisms and technical means used in its implementation but it has faced and still face several challenges and obstacles when the application will explain in the body of the study. The study concluded that the application of the draft e-Algeria in 2013 is associated with overcoming the challenges and the stakes that stands in front of this project, which needs to be more effective so that it can perform its role in the service of Algerian citizens and the promotion and development of the national economy and overall development Among the most immediate uses of electronic government in Algeria are: card healing, magnetic card (yellow), electronic payment card (gold card), G3, G4, biometric passport and biometric identification card, technology devices in national security.
Keywords: الإدارة الإلكترونية -- حوكمة المؤسسات -- السياسات العامة -- الجزائر